Studying The Characteristic Parameters and External Freedom Degree of Polyethylene in different Molecular Weights By Hole Theory - Shanay Rajab Hasan; Saygin M. Nuri (Tikrit Journal of Pure Science)
The external degree of freedom of linear and branched molecules of polymers played an important role in new polymer synthesis. The theory Simha-Somcynsky (SS) which established for the first time the statistical thermodynamics and polymers state of equation, using the mean field theory )that does not depend on the structural of materials). Expressed through the zeroth-order mean field theory through the hole vaccume cells as a measure of irregularity in the lattice. The (SS) theory has achieved quantitative success in statistical thermodynamics of polymers.  The SS theory has been applied to extract the external degrees of freedom for polyethylene at different molecular weights. The external degree of freedom is very important parameter to specify the thermodynaics characteristic parameters. Applying SS hole theory, the thermodynamic properties of polyethylene was studied for temperature from 353K up to 473 and pressure from o.1Mpa up to150 Mpa. The minimum and maximum deviations in specific volume was found to be  0.045 (PE2100) and 1.138 (PE156) respectively..